The Effectiveness of Anti-Inflammatory Cream Galenic Preparations Based on Snail Seromucoid, Durian Peel Extract Polysaccharides and Chitosan in the Wound Healing Process (In Vivo) - Harti, Agnes Sri; Sutanto, Yusup Subagio; Agustin, Wahyu Rima; Putriningrum, Rahajeng; Irdianty, Mellia Silvy; Saelan, Saelan; Ardiani, Nurul Devi (International Journal of Public Health Excellence (IJPHE), 2024)
Development of galenic preparation formulations that can be used to make anti-inflammatory cream preparations. Snail seromucoid contains glycoproteins, mannose carbohydrates, glucose, N-acetyl muramic acid and the α-1 globulin-oromucoid fraction which functions as a bioimmunostimulator. Durian peel (Durio zibethinus L.) contains a polar polysaccharide polymer compound such as D-galacturonic acid which has anti-microbial properties. Chitosan is a polymer compound resulting from derivatization of chitin which has antimicrobial polycationic properties; biodegradable, and biocompatible with animal body tissue. The aim of the research was to examine the effectiveness of a galenic anti-inflammatory cream preparation based on snail seromucoid, durian skin extract, and chitosan for healing acute and chronic wounds in vivo. The research method is experimental research, namely the effectiveness of anti-inflammatory galenic cream preparations made from snail seromucoid, durian peel extract and chitosan on various types of wounds in vivo. Analysis of observation data using the one way anova test. A galenic preparation based on a combination of 2% snail seromucoid, 2% durian peel extract polysaccharide and 2% chitosan ratio 1:1:1 is effective in the healing process based on the formation of granulation tissue thickness in incision injuries, hot objects injuries, second degree burns and ulcers. diabetes. The bioformulation galenic preparation of 2% snail seromucoid, 2% polysaccharide of durian peel extract; 2% chitosan and their combination with ratio 1:1:1 is effective as an anti-inflammatory galenic cream preparation so that it can be applied for healing chronic wounds, acute wounds and diabetic ulcers.